What makes a leader? - Goleman, Daniel (Boston, Massachusetts : Harvad Business Review Press, 2017)
Psychologist and author Daneil Goleman found that truly effective leaders are distinguished by a high degree of emetional intellitence. A person can have first-class training , an incisive mind, and and ensless supply of goods idear, but without emotional intellitence that person can never be a great leader. The cheif component of emotional intelligence-self-awareness, self-regulation, motivation, emphathy, and social skill-can sound unbusinesslike, but emmotional intelligence drives measurable business results. This, the define article on the subject, provides a detailed discussion of each component of emotional entelligence, how to recognize it in potential leaders, how and why it connects to performence, and how it can be leaderned.
Tặng
Keywords: Leadership; Emotional